Toll-like receptors, cytokines & nitric oxide synthase in patients with otitis media with effusion - Lee, Ho Yun (Medknow Publications & Media Pvt Ltd, 2013)
BACKGROUND & OBJECTIVES: Microbial infections in the normally sterile environment of the middle ear cavity in patients with otitis media trigger expression of Toll-like receptors (TLRs), cytokines, and nitric oxide. We evaluated the expression levels of TLR-1, -2, -4, -5, -6, and -9, interleukin (IL)-6, -8, -10, and -12, interferon-γ (IFN-γ), tumour necrosis factor-α (TNF-α), and nitric oxide (NO), in paediatric patients with otitis media with effusion (OME). METHODS: The levels of TLR, cytokine, and nitric oxide synthase (NOS) mRNAs in middle ear effusion were assessed by real-time polymerase chain reaction in 96 children with OME, 24 prone and 72 not prone to otitis. The level of expression of each mRNA was compared in the otitis-prone and non-otitis-prone groups, in patients with and without bacteria, and by frequency of ventilation tube insertion. RESULTS: The expression of TLR-1, -2, -4, -5, -6, and -9; IL-6, -8, -10, and -12; IFN-γ; TNF-α; and NOS mRNAs in the effusion fluid of both the otitis-prone and non-otitis-prone groups were measured. The expression levels of TLR-2, -4, -6, and -9 mRNA were significantly lower in the otitis-prone than in the non-otitis-prone group (P<0.05). Although higher levels of TLR, cytokine, and NOS mRNAs were generally observed in culture positive than in culture negative patients, none of these differences was statistically significant. No differences were observed in the expressions relative to the frequencies of ventilation tube insertion. INTERPRETATION & CONCLUSIONS: TLRs, cytokines, and NOS, which act cooperatively in the innate immune response, were closely associated with OME. Decreased expression of TLRs may be associated with increased susceptibility to OME.